2018
DOI: 10.1016/j.jpor.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of complete dentures based on digital intraoral impressions—Case report

Abstract: This case demonstrated how digital complete dentures can be made without requiring conventional stone models or mounting the models in an articulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…To date, the use of optical impressions in removable prosthodontics derives from a growing interest in a complete digital workflow for the production of complete dentures [14][15][16][17][18]. Although a few anecdotal studies discussed the use of optical impressions on fully edentulous arches [31,32], according to Mangano et al [33], to date the use of IOSs is contraindicated for the fabrication of complete removable dentures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the use of optical impressions in removable prosthodontics derives from a growing interest in a complete digital workflow for the production of complete dentures [14][15][16][17][18]. Although a few anecdotal studies discussed the use of optical impressions on fully edentulous arches [31,32], according to Mangano et al [33], to date the use of IOSs is contraindicated for the fabrication of complete removable dentures.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, there has been growing interest in a full-digital concept of complete dentures focusing on the use of optical impressions in the field of removable prosthodontics [14][15][16][17][18]. The protocol for a digitally produced complete denture starts with the digitization of an edentulous arch that can be performed using intraoral or laboratory scanners.…”
Section: Introductionmentioning
confidence: 99%
“…In order to directly obtain digital intraoral impressions of the maxilla, the operator used his left-hand thumb and forefinger to retract the lip, cheeks and vestibule, exposing the greatest amount of the surface area of the vestibule; then a second operator separated the upper and the lower jaws using their fore and middle fingers as bite blocks and, with the other hand, cleaned and dried the area to be scanned with a sterile gauze. Considering the dimension of the scanner (CS 3600, Carestream Dental, Atlanta, GA, USA) head compared to the small patient mouth, the IOS itself acted as a bite block during the scanning procedure, which was performed quickly by rotating it from left to right on the palatal side and then sliding it along the edentulous ridge vestibular aspect from the right to the left distobuccal areas [34]. The scanner head was pre-heated, dipping it, while still in the sealed sterile envelope, in 38 • C water; the entire impression procedure took less than thirty seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a comparative study on the differences between impressions obtained through the various techniques is needed. Studies including a digitized device and software have been reported;22232425 the method employed was to scan the target objects using a scanner and overlay the acquired images using software in order to compare the differences 25. The technique of superimposition is simple, reliable, and has been used in several recent studies 2627.…”
Section: Introductionmentioning
confidence: 99%